Adapting Agile Practices to Improve the Quality of Small and Medium Scale Organizations - Naseer, H.; Hafeez, Y.; A. Arshad, W. A. (The Nucleus, 2018)
Most of the Software industries are demonstrating absorption in Software Process Improvement (SPI) in Small and Medium Enterprises. In the modern world, software development and improvement is an important area that permits organizations to develop applications in house. Traditionally, waterfall system is used to administer software development. The traditional, waterfall model counted upon linear, sequential stages, well explained features, sign of documentation and widespread coverage. The outcome of the study is to formulate a holistic model for customization of agile practices for small and medium organizations. This paper has demonstrated a case study emphasizing on tailoring agile methods including tailored XP (extreme programming) focusing Small and Medium Enterprise (SME) for software process improvement. This framework is for software processes being implemented by SME merging agile methods XP, Scrum and defines the handover in pre-transition and post order.